Push-Type Rotary Steering Mandrel Mechanical Analysis and Life Prediction - Li, Wenzhe; Chen, Ye; Zhang, Jichuan; Wang, Xudong; Wu, Pengcheng; Ma, Chengyu; Wan, Xiumei; Chen, Xing (Manufacturing Technology Journal, 2025)
The push-type rotary steerable core bearing has high load capacity and high precision, and has been widely used in oil and gas drilling field. Its service life is difficult to predict due to various complex working conditions. Based on the finite element method, this paper establishes a three-dimensional rotating guide mandrel model to calculate and analyze the mechanical simulation of the guide mandrel under different working conditions, and establishes the corresponding life prediction model to predict its life. The results show that reducing the torque and speed in the range of drilling requirements is conducive to improving the overall life of the spindle, and the life matrix and life distribution are consistent with the characteristics of S-N curve, which is consistent with the characteristics of high cyclic stress of the spindle. The research results can be used to reliably predict the life of the push-type rotary steering mandrel and simulate its working state with high precision. This data is critical for reliability analysis and design optimization.
Keywords: Rotary steerable system; Finite element method; Life prediction; S-N fatigue